The Dialectics of Islamic Law and Customary Law on Marriage Concept of Javanese Muslim in Malaysia - Fitri Rafianti; Arik Dwijayanto; Azharuddin Mohd Dali (Justicia Islamica, 2021)
In Malaysia, customary law, especially marriage, should follow Islamic laws. Customary law should not conflict with Islamic law. On the contrary, the Muslim community of Javanese descent in Malaysia can combine customary and Islamic laws balanced. They maintain Javanese marriage traditions by harmonizing Malay customs and Islamic marriage laws, such as rewang (helping each other), slametan (praying together), tunangan (engagement), ijaban (wedding), and nyumbang (donating).  To contribute to previous studies, this article aims to critically examine the debate between customary and Islamic laws regarding the marriage tradition of the Javanese Muslim community in Selangor and Johor, Malaysia. The analysis results show that the debate of customary and Islamic laws concerning the concept of marriage for the Javanese Muslim community in Malaysia encourages negotiations so customs in harmony with Islamic law can be maintained and conflicting traditions can be abandoned. The debate between customary and Islamic laws in the marriages of Javanese Muslim communities in Malaysia is closely related to social, economic, and traditional symbols of carrying out religious teachings, strengthening solidarity, and preserving tradition.